Proyecto de factibilidad para la creación de una empresa de procesamiento y envasado de “agua natural” y su comercialización en la ciudad de Portoviejo, provincia de Manabí - Páez Cárdenas, Ludy Paulina (2015)
The general objective of this thesis is to create a business Processing and Packaging of "Natural Water" and marketing in the city of Portoviejo, Manabí, which allowed the application of different methods and techniques that research permits as the Deductive Method, the Inductive Method, Analytical Method, The Synthetic Method, Statistical Method; further research techniques were applied as the survey and literature review. A total of 399 surveys to people in 185 establishments Portoviejo and sale of natural water are made, In the market study conducted47.910.799 unmet demand for water bottles 500ml for the market town of Portoviejo was determined The technical study enabled a capacity utilization of 291.200 bottles of water which is 70% of the installed capacity of the company for the first year of the project. The financial study determinedan investment of 31.137,38 dollarwat contributions from partners anda bank loan.Financial of 10.000 dollar, evaluators founda NPVof116.843,40aCapitalRecovery Period1 years, 4 months and 23days,the benefit-cost ratioof 1,40 centsmeaning thatfor every dollar investedwill earn40 cents, and IRR of59.08% and a sensitivity analysissupportsan increase in costsof19,20% and a decrease in revenuesof 14,10%. These indicator sanalyze the projectis feasible torealizein the city of Portoviejo. Finally the respective conclusions of the research Project andtheir recommendationswere analyzed